Interventional radiology: Diagnosis and treatment of post-traumatic nonischemic priapism: A case report - Nazim Lounici, MD; Ammar Maireche, MD; Abdelouahab Cheifa, MD; Mohammed Rafiq Saadat, MD; Souad Sahbane, MD; Karima Seddiki, MD (Radiology Case Reports, 2024)
Priapism is defined as a form of erectile dysfunction characterized by a prolonged and involuntary penile erection, either partial or complete, occurring without sexual stimulation and lasting for more than 4 hours. Its incidence is estimated to be 0.5-0.9 cases per 100,000 people per year.The most frequent form is ischemic priapism, results from paralysis of the cavernous smooth muscles, which are unable to contract, leading to the stagnation of hypoxic blood within the sinusoidal spaces. Characterized by a painful rigid and sustainable erection.Non-ischemic priapism constitutes a rare entity, unlike the former, this type is typically painless. It is caused by an excessive influx of blood into the penis without a concomitant increase in outgoing blood flow. Blunt trauma is the most commonly reported etiology.And finally, recurrent priapism is characterized by recurrent episodes of prolonged erection and can be challenging to treat, often requiring long-term management to prevent recurrences.We report a case of high-flow priapism in a 10-year old child, secondary to a cavernous arterial fistula following a straddle injury during sports activity. It was suspected clinically and confirmed by ultrasound-Doppler, then successfully treated radiologically with highly selective embolization, with very satisfactory postoperative outcomes.